Comics will break your heart - Hicks, Faith Erin (Square Fish, 2020)
She could've been rich if Miriam's grandfather, co-creator of the hit comic series Tomorrow-Men, hadn't sold his share of the company to his partner back in 1960. Now she's worried about how she'll pay for college. To complicate matters, a new, attractive boy shows up in town who just so happens to be the grandson of the man who "stole" Miriam's future, and is now heir to the Tomorrow-Men fortune. Long-held bitterness notwithstanding, Miriam is disappointed to find herself falling for the handsome boy.